2020
DOI: 10.1002/gps.5274
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairment and Alzheimer's disease pathology in individuals with MCI who underestimate or overestimate their decline

Abstract: Objectives The aim of this study was to examine whether the discrepancy between participant and informant estimation of memory decline can predict MCI prognosis. Methods Analyses involved data from individuals with MCI enrolled in the Alzheimer's Disease Neuroimaging Initiative (ADNI) who filled the Everyday Cognition questionnaire. Participants who underestimated (N = 112) and overestimated (N = 157) their memory decline were compared on memory tasks, brain volume, and cerebrospinal markers, at study entry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Although this result does not appear to be in line with expected cognitive alterations in MCI, it is the intensity of the subjective complaint in language and in general health that is assessed in our study, and subjective complaint reported by participants with MCI may have less signification. Indeed, brain alterations can be already present in MCI, and individuals with MCI can have less self‐awareness of their troubles, that is, anosognosia 39 . Gifford et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this result does not appear to be in line with expected cognitive alterations in MCI, it is the intensity of the subjective complaint in language and in general health that is assessed in our study, and subjective complaint reported by participants with MCI may have less signification. Indeed, brain alterations can be already present in MCI, and individuals with MCI can have less self‐awareness of their troubles, that is, anosognosia 39 . Gifford et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, brain alterations can be already present in MCI, and individuals with MCI can have less self-awareness of their troubles, that is, anosognosia. 39 Gifford et al showed that subjective cognitive complaint reported by individuals with MCI did not predict conversion to dementia. 18 In the analysis by ROIs, several associations were found different between participants with iSCC or MCI, meaning that the cognitive status may more modulate the associations between brain biomarkers and subjective complaint scores when the brain is studied by ROIs.…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant difference in the neuropsychological scores between MCI-A and MCI-NA was found, MCI-A had a tendency of decreased memory performance compared with MCI-NA. Previous research has confirmed that MCI-A performs worse on memory-related scales (Bregman et al, 2020 ). In this study, although no significant difference in memory performance between the MCI-A and MCI-NA was found, the activity strength of the precuneus brain area between the two groups has already been significantly different.…”
Section: Discussionmentioning
confidence: 74%
“…Lastly, considering the sample is comprised of pwMCI, it is plausible to question the validity of a person's rating of their confidence in performing memory‐related activities when they themselves have varying insight into these memory difficulties. For instance, recent findings suggest that identifying pwMCI who underestimate their cognitive abilities may serve as a prognostic variable of Alzheimer disease pathology and cognitive severity 38 . Yet, confidence in one's ability to complete a task, no matter if it is an overestimation or underestimation of true ability, might be a variable of at least equal interest to measuring cognition objectively.…”
Section: Discussionmentioning
confidence: 99%